Team Games Tournament (TGT) Learning Model with a Medium Box Instrument to Improve Student’ Learning Outcomes - Siregar, Happy; Toruan, Jagar; Ardipal, Ardipal; Syeilendra, Syeilendra (Indonesian Research Journal in Education |IRJE|, 2024)
This research aims to improve the learning outcomes of the students in class VIII-B at SMP Plus Taruna Andalan Pangkalan Kerinci in the Traditional Musical Instrument Classification subject through the Team Games Tournament (TGT) learning model supported by media box instrument. This research uses the Classroom Action Research (CAR) method with four stages: planning, action, observation, and reflection. The research results show that the Team Games Tournament (TGT) learning model with a media box instrument can improve students' learning outcomes. In cycle I, 50% of students achieved the Minimum Completeness Criteria (KKM) score, with an average class score of 74.68. This result shows a significant improvement compared to the learning outcomes before the action (pre-cycle), which only reached 25% of students achieving the KKM. This research concludes that the Team Games Tournament (TGT) learning model with the media box instrument is effective in enhancing student understanding and learning outcomes in the Traditional Musical Instrument Classification subject. This learning model encourages students to participate actively, improves learning motivation, and creates a fun and engaging learning environment.